2023
DOI: 10.3390/molecules28093953
|View full text |Cite
|
Sign up to set email alerts
|

Untreated Opuntia ficus indica for the Efficient Adsorption of Ni(II), Pb(II), Cu(II) and Cd(II) Ions from Water

Abstract: The raw cladode of Opuntia ficus indica (OFI) was evaluated as a sustainable biosorbent for the removal of heavy metals (Ni, Pb, Cu, and Cd) from aqueous solutions. The functional groups of OFI were identified by employing DRIFT-FTIR and CP-MAS-NMR techniques before and after contact with the ions in an aqueous media, showing a rearrangement of the biomass structure due to the complexation between the metal and the functional groups. The adsorption process was studied in both single- and multi-component system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…The FT-IR spectral analysis ( Fig. 2 ) reveals various absorption peaks, each corresponding to specific molecular vibrations [ 14 , [19] , [20] , [21] ]. Within the range of 3700–2500 cm −1 , a broad absorption band is observed, indicating the intramolecular vibrational stretching of the –OH groups, which are extensively engaged in hydrogen bonding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FT-IR spectral analysis ( Fig. 2 ) reveals various absorption peaks, each corresponding to specific molecular vibrations [ 14 , [19] , [20] , [21] ]. Within the range of 3700–2500 cm −1 , a broad absorption band is observed, indicating the intramolecular vibrational stretching of the –OH groups, which are extensively engaged in hydrogen bonding.…”
Section: Resultsmentioning
confidence: 99%
“…To gain a comprehensive understanding of its potential as P adsorbent, we subjected both the chemically treated biomass with Ca 2+ , Fe +2 and Fe 3+ , and the untreated biomass using the Fourier-transform infrared spectroscopy (FT-IR). We followed the methodology outlined by Barbera et al [ 14 ] albeit with a primary focus on evaluating the functional groups responsible for the interaction between the biomass and phosphate ions. Spectra are in the range 4000–400 cm −1 obtained by a PerkinElmer FT-IR spectrometer Spectrum Two.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have reported that the juice of cladodes can counteract the effects generated by many toxic substances, including heavy metals [21]. Cladodes also possess neuroprotective effects, reducing excitotoxic damage caused by ischemia and inflammatory neuronal damage [22].…”
Section: Introductionmentioning
confidence: 99%